Modelling the impact of performance management practices on firm performance: Interaction with human resource management practices - Pavlov, Andrey; Mura, Matteo; Franco-Santos, Monica; Bourne, Mike (Taylor & Francis, 2017)
The paper draws on resource orchestration theory to investigate whether and how performance management (PM) practices interact with human resource management (HRM) practices in organisations as well as how this interaction affects firm performance. The proposed theoretical model was tested through a survey of 192 UK firms using Partial Least Squares approach for structural equations modelling. The findings show that the effect of PM practices on firm performance is better explained when the interaction between these practices and other organisational practices is considered. In particular, we examine the extent to which the interaction between PM practices and commitment-based HRM practices affects performance. We find that when HRM practices and PM practices are misaligned, their effect on performance can be negative. This is the first paper in the PM literature that establishes the relationship between PM and HRM practices in organisations and demonstrates the effect of this relationship on firm performance
Keywords: Performance management; performance measurement; human resource management; survey; partial least squares